Hungaricum as a quality of fruits and fruit products - Soltész, M.; Nyéki, J.; Szabó, Z.; Papp, J. (International Journal of Horticultural Science, 2003)
The territory of the Hungarian state is largely suitable for the purpose of growing fruits of the temperate zone species. During the next decennia, the annual volume of Hungarian fruit production is expected to be around 1.1-1.3 million tons, from which some 15% is considered to be a produce of Hungary or "Hungaricum" (90 thousand tons of sour cherry, 50 thousand tons of apricot, 20 thousand tons of raspberry, 10 thousand tons of walnut). These fruits symbolise the country's special quality, which are worth to catch the interest the foreign consumers.The category of Hungaricum involves almost exclusively varieties of Hungarian origin as sour cherries, apricots, raspberries and walnuts, and they are representing outstanding qualities on the international markets.As for the fruit products the fruit brandies are eligible to be "Hungaricum" and are called exclusively "Pálinka". The Pálinka, provided to be distinguished with a geographic mark and will be competitive on the world market. Smaller quantities, though significant produce is represented by the deep frozen raspberry.